1999
DOI: 10.1002/(sici)1097-0339(199907)21:1<4::aid-dc2>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Pap smear follow-up of possible role of mucopurulent exudate as a prognosticator of a negative pregnancy outcome

Abstract: Our objective was to study a cohort of women by various means to detect sexually transmitted diseases (STD) and to correlate the presence of mucopurulent exudate (PEX) on Papanicolaou (Pap) smears with pregnancy outcome. Bacteriologic cultures taken from swabs for chlamydia and gonorrhea were correlated with GenProbe results. Smears were examined for trichomonas, yeast, HPV, obscuring mucopurulent exudate, and squamous intraepithelial abnormalities. There was no positive correlation between STD and negative pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In addition, Prey 21 reported the necessity of the presence of coccobacilli-type microorganisms for the diagnosis of BV by Pap smear. Bedrossian and colleagues 22 reported that Pap smear gives results as good as Gram stain in the diagnosis of BV and cervicitis. They also reported that the exclusion of Gram stain from the routine examination method might decrease the economic cost.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Prey 21 reported the necessity of the presence of coccobacilli-type microorganisms for the diagnosis of BV by Pap smear. Bedrossian and colleagues 22 reported that Pap smear gives results as good as Gram stain in the diagnosis of BV and cervicitis. They also reported that the exclusion of Gram stain from the routine examination method might decrease the economic cost.…”
Section: Resultsmentioning
confidence: 99%
“…16 In this study, prevalence of abnormal smears was correlated with the risk factors including age, parity, residence area, gestational age, gravidity, socio-economic status, occupation, age at first intercourse, number of sexual partners, smoking, history of contraception. There were 152 (50.67%) abnormal smears including inflammatory smears, whose significance has been a matter of much interest in relation to pregnancy complications and is being currently studied.…”
Section: Discussionmentioning
confidence: 95%
“…Dear Dr. Bedrossian: The series of articles recently published concerning the cytologic diagnosis of bacterial vaginosis (BV) [1][2][3][4] has spurred me to express some considerations on this important subject, given that we were among the first to stress the use of the Pap smear for the diagnosis of BV in this journal in 1987. 5 BV is neither a nonspecific vaginitis nor a single microorganism vaginitis as Gardner and Dukes 6 first thought and now many clinicians and some pathologists continue to use the term Gardnerella vaginitis.…”
mentioning
confidence: 99%